The sum of the sequence based on the function Sn = ( -1 )n + 1 will be -6.
<h3>How to depict the information?</h3>
The formula for finding the nth term in an arithmetic sequence given as:
= a + (n - 1)d
Here, Sn is given as ( -1 )n + 1. This is used to illustrate the sum in the sequence. Based on the function given, let's assume that n = 5. Therefore, the 5th term will be:
= (-1)n + 1
= (-1)5 + 1
= (-1)6
= -6
Here is the complete question:
Find the 5th term of a sequence given the function Sn = ( -1 )n + 1.
Learn more about sequence on:
brainly.com/question/6561461
#SPJ1